1997
DOI: 10.1021/js960283m
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Insect Repellent N,N-Diethyl-m-toluamide in Beagle Dogs following Intravenous and Topical Routes of Administration

Abstract: The common topical insect repellent N,N-diethyl-m-toluamide (DEET) has caused serious adverse effects in the users of DEET products due to its high skin permeability. This study investigated the pharmacokinetics of DEET following i.v. and dermal routes of administration in beagle dogs. The pharmacokinetics of DEET was linear over the dose range of 2.5-6.0 mg/kg. Following the i.v. dosing, plasma DEET concentrations declined biexponentially with an elimination half-life of 2.56 h. Volume of distribution at stea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 18 publications
(23 reference statements)
1
18
0
Order By: Relevance
“…DEET underwent metabolic transformation mediated by esterases and cytochrome p450 enzymes, resulted in formation of metabolites of w-toluic acid and m-toluamide. This is in agreement with previous reports following dermal dose of DEET in rats and dogs Qiu et al, 1997), and in accordance with previous studies reported that DEET metabolism mediated by iV-dealkylation, ring hydroxylation and ring dealkylation following in vitro incubation with rat liver microsomes (Constantino and Iley, 1999;Taylor, 1986). These findings are also consistent with our recent results obtained following in vivo and in vitro incubation of DEET with human liver microsomes (Abu-Qare and Abou- Donia, 2001b;2001d).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…DEET underwent metabolic transformation mediated by esterases and cytochrome p450 enzymes, resulted in formation of metabolites of w-toluic acid and m-toluamide. This is in agreement with previous reports following dermal dose of DEET in rats and dogs Qiu et al, 1997), and in accordance with previous studies reported that DEET metabolism mediated by iV-dealkylation, ring hydroxylation and ring dealkylation following in vitro incubation with rat liver microsomes (Constantino and Iley, 1999;Taylor, 1986). These findings are also consistent with our recent results obtained following in vivo and in vitro incubation of DEET with human liver microsomes (Abu-Qare and Abou- Donia, 2001b;2001d).…”
Section: Discussionsupporting
confidence: 93%
“…It seems that dose, and route of administration of DEET were factors in the determination of its pharmacokinetic profile and its rate and pattern of elimination. Qiu et al (1997) reported that the pharmacokinetic profile of DEET was bei-exponential with an elimination half-life of 2.7 h, after dermal dose in Beagle dogs, where its plasma concentration peaked 1-2 h after dosing. Furthermore reported that blood serum concentration of DEET was 12347 ng/ml following an i.p injection of 500 mg/kg in male rats.…”
Section: Discussionmentioning
confidence: 99%
“…26 Designed as topical agents, repellents and sunscreens under ideal application conditions should exert minimal transdermal and systemic absorption. Animal 27,28 and human 29 studies have indicated that when individually applied, DEET is capable of transdermal and systemic absorption. Furthermore, studies with human volunteers have indicated that oxybenzone is also capable of transdermal and systemic absorption.…”
Section: Safetymentioning
confidence: 99%
“…1b) is an essential UVA/UVB blocking agent that is extensively used in commercially available sunscreen products [3,4]. Systemic absorption of both compounds after topical applications has been separately studied [5][6][7]. Recently we reported a synergistic percutaneous permeation between DEET and oxybenzone after the two active ingredients were used simultaneously in vitro [8,9].…”
Section: Introductionmentioning
confidence: 99%